Domino liver transplantation for select metabolic disorders: Expanding the living donor pool. Issue 1 (19th June 2019) - Celik, Neslihan; Squires, James E.; Soltys, Kyle; Vockley, Jerry; Shellmer, Diana A.; Chang, Wonbae; Strauss, Kevin; McKiernan, Patrick; Ganoza, Armando; Sindhi, Rakesh; Bond, Geoffrey; Mazariegos, George; et al.
Abstract: Domino liver transplantation (DLT) involves transplanting liver from a patient with metabolic disease into a patient with end‐stage liver disease with the expectation that the recipient will not develop the metabolic syndrome or the recurrent syndrome will have minimal affect. The domino donor gets a deceased donor or a segment of live‐donor liver through the deceased donor organ allocation system. Waitlist mortality for the domino recipient exceeds morbidity associated with getting the donor disease. Between 2015 and 2017, four patients with three metabolic disorders at UPMC Children's Hospital of Pittsburgh underwent DLT with domino allografts from maple syrup urine disease (MSUD) patients. These included patients with propionic acidemia (PA) (n = 1), Crigler‐Najjar (CN) syndrome type‐1 (n = 2), and carbamoyl phosphate synthetase deficiency (CPSD) (n = 1). Mean follow‐up was 1.6 years (range 1.1‐2.1 years). Total bilirubin levels normalized postoperatively in both CN patients and they maintain normal allograft function. The PA patient had normal to minimal elevations of isoleucine and leucine, and no other abnormalities on low protein diet supplemented with a low methionine and valine free formula. No metabolic crises have occurred. The patient with CPSD takes normal baby food. No elevation in ammonia levels have been observed in any of the patients. DLT for a select group of metabolic diseases alleviated the recipients of their metabolic defect with minimal evidence of transferrable‐branched chain amino acid elevations or clinical MSUD despite increased protein intake. DLT using allografts with MSUD expands the live donor liver pool and should be considered for select metabolic diseases that may have a different enzymatic deficiency.